Elemental Distribution in Tissues of Shorthorn Sculpins (Myoxocephalus scorpius) from Kongsfjorden in Svalbard - Francisco Ardini; Federico Moggia; Davide Di Blasi; Paola Rivaro; Marco Grotti; Laura Ghigliotti (Journal of Marine Science and Engineering)
The shorthorn sculpin (Myoxocephalus scorpius) is considered a suitable sentinel species for marine pollution in the Arctic due to its ecology and stationary habits. To evaluate its role as a bioindicator for potential natural and anthropic impacts on the marine ecosystem of the Kongsfjorden (Svalbard, Norwegian Arctic), 33 female and male specimens of shorthorn sculpins were collected in July 2018 in proximity of the Ny-Ålesund international research facility and analyzed for the content of 25 major and trace elements and methylmercury (MeHg) in the muscle, liver, gonads, and gills by using spectroscopic techniques. Most elements had their maximum average concentrations in the gills (Al, Cr, Fe, Mn, Na, Ni, Pb, Se, Si, Sr, and V), while the livers featured higher contents of some toxic and heavy metals (As, Cd, Cu, Mo, and Zn). The muscle was characterized by high contents of Ca, K, and Mg, while Ba, Co, and P were mostly concentrated in the gonads. The gonads presented higher concentrations of Cr, K, Mg, Ni, P, and V for the males and Co, Cu, Fe, Mn, and Se for the females. Both the total Hg and MeHg concentrations in the muscle correlated with the fish size, indicating bioaccumulation, although high Se/Hg molar ratios (11.0 ± 2.2) suggested a low toxic potential of mercury.